Against a Migrant Cinema. Critical Reflections on the Postcolonial Perspective - Raffaele Pavoni (Cinergie, 2019)
“What? You did not include any reference to the Tahrir Square uprising?” In the final scene of La Vierge, les Coptes et Moi (Namir Abdel Messeeh, 2012), an autobiographical film in which the director, an Egyptian Copt residing in France, stages the alleged apparition of the Madonna in his native village, the (French) producer blurts out, reproaching the director for speaking about himself, and not about the political situation in his country. That same year, Tahrir, by the Italian Stefano Savona, documented masterfully that social reality, with an insider's eye, although the author was a foreigner. This discomfort of the autochthonous, for which the foreign filmmaker is admitted only to the extent that he tells us of his “strangeness”, calls into account the cinephile approach, intimately Eurocentric, to the “marginal” cinemas. To seek an image “Other”, indeed, would do nothing but replicate, by its very nature, the alterity it attempts to eliminate: it is a paradox that seem to characterise part of the European contemporary cinema (Capussotti 2009; Cincinelli 2009; Corrado, Mariottini 2013, Garosi, Trapassi 2016; De Franceschi 2013; Jedlowski 2001; Schrader, Winkler 2013) and literature (Fracassa 2012; Negro 2015, Proglio 2011; Romeo 2018). This has given rise to a re-evaluation of postcolonial studies, applied to the film studies (Heffelfinger, Wright 2011; Ponzanesi, Waller 2012). The minimal common denominator of both domains seems to be the notion of gaze, with the subtle ambiguity that this approach entails: the “Other” is, by definition, “other than Us” (Baggiani, Longoni, Solano 2011). The process of othering intrinsic in any European view of the “Other”, being Eurocentrism not a rhetorical choice but an inescapable perspective (Shohat / Stam 1994), is therefore a double-edged sword: on the one hand it tends to recognise the specificity of non-European cinematographic forms, questioning some aesthetic and narrative rules of “western” cinema (where the very notion of "West", as Said notes, is intimately Eurocentric) (1978). On the other hand, this risks to flatten the “Other” to his own culture of belonging, forcing the will of non-European directors to express themselves exclusively within more or less conscious processes of media segregation, that prevent the expression of a subjective gaze (De Franceschi, 2018). The very notion of “migrant cinema”, therefore, on the one hand tends to historicize a phenomenon, recognizing in the current socio-political context a common ground on which such products, despite their diversity, can grow; on the other hand, like any codification, this historicization tends to bring back to the collective sphere what is often an individual artistic expression: as it does not speak of society, it is simply not interesting. In this sense, as we will try to argue in this essay, the postcolonial perspective on the one hand proves to be effective, as it opens up film studies to important methodological contaminations; on the other hand, as a negative consequence, it tends to treat “migrant cinema” as a genre in its own right, thus transforming the “eye of the migrant” into an “eye on migrant”. In a critical-theoretical perspective, this paper will debate on how the denial of the existence of a migrant cinema is not an attempt to deconstruct a consolidated historiographical frame, but on the contrary, it is a way to avoid that this historicization implies and replicates the same dynamics of abjection that it tends to eliminate.